Leksikon Klasik pada Permainan Anak di Masyarakat Budaya Minangkabau - Rona Almos; Sonezza Ladyanna (Universitas Andalas, 2021)
The lexicon is an important part of the heritage of local wisdom which is also important in culture-based children's education. This article, it is explained the classic lexicon of children's games in Minangkabau culture and the cultural significance of the lexicon. This research was conducted through quantitative and qualitative methods. Sources of data in this study are edited ancient manuscripts, documentation of folklore, and traditional holders in Minangkabau culture. The data were analyzed through an anthropolinguistic approach. The classic lexicon of children's games in Minangkabau culture are boborea, sapu-sapu rangik, and tang-tang buku, ulo-ulo, dama, and badie balantak. The classical lexicon must be maintained because it has cultural significance for the Minangkabau people who have a sense of togetherness, shrewdness, and strong intelligence in thinking and must be familiar with children from an early age through education, one of which is through games. In addition to technological developments and lifestyle changes, the Covid-19 pandemic has also affected the way children play.